Österreichs Glorie am Trogerhimmel - Lechner, Gregor Martin,Rameder, Bernhard,Troger, Paul (Benediktinerstift Göttweig, 2012)
Literaturangaben
Keywords: Katalog; Troger; Paul; Church decoration and ornament; Mural painting and decoration; Baroque